20th Anniversary of Pharmaceuticals (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
The Special Issue Reprint encompassing peer-reviewed articles on glaucoma and neuroprotection is timely, as the constellation of eye diseases is ever-increasing as the world’s population ages. The aim of the Special Issue was to capture some leading aspects of on-going research into pathophysiology, genetics and current and future therapeutic treatment options to mitigate the signs and symptoms of these potentially blinding disorders, especially open-angle and normotensive glaucoma that affect millions worldwide. I hope that this collection of original research and review articles will spur further interest in these elements in the academic arena and in the biopharmaceutical industries.